Identification of Novel Chemical Scaffolds that Inhibit the Growth of Mycobacterium tuberculosis in Macrophages - Ahmed, Sara; Manning, Alyssa; Flint, Lindsay; Awasthi, Divya; Ovechkina, Yulia; Parish, Tanya (Frontiers in Pharmacology, 2022)
Mycobacterium tuberculosis is an important global pathogen for which new drugs are urgently required. The ability of the organism to survive and multiply within macrophages may contribute to the lengthy treatment regimen with multiple drugs that are required to cure the infection. We screened the MyriaScreen II diversity library of 10,000 compounds to identify novel inhibitors of M. tuberculosis growth within macrophage-like cells using high content analysis. Hits were selected which inhibited the intramacrophage growth of M. tuberculosis without significant cytotoxicity to infected macrophages. We selected and prioritized compound series based on their biological and physicochemical properties and the novelty of the chemotypes. We identified five chemical classes of interest and conducted limited catalog structure-activity relationship studies to determine their tractability. We tested activity against intracellular and extracellular M.tuberculosis, as well as cytoxicity against murine RAW264.7 and human HepG2 cells. Benzene amide ethers, thiophene carboxamides and thienopyridines were only active against intracellular bacteria, whereas the phenylthiourea series was also active against extracellular bacteria. One member of a phenyl pyrazole series was moderately active against extracellular bacteria. We identified the benzene amide ethers as an interesting series for further work. These new compound classes serve as starting points for the development of novel drugs to target intracellular M. tuberculosis.